2020
DOI: 10.1007/s12298-019-00750-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different seed priming techniques on oxidative and antioxidative responses during the germination of Oryza sativa varieties

Abstract: NaCl and PEG stresses have negative impacts on seed germination and early seedling establishment in Oryza sativa. The present study was designed to ascertain the influence of different priming techniques (Hydro priming-HyP, Halo priming-HP, UV-B priming-UP) in enhancing oxidative and anti-oxidative mechanisms during seed germination phase in response to NaCl and PEG stresses tolerance of three rice varieties (Neeraja, Vaisakh and Vyttila 6). NaCl and PEG stresses caused delayed germination rate, enhanced react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…The present study revealed that primed seeds (HA and HP primed for 3 h and 5 h) had reduced amount of MDA content compared with non-primed seeds believed to be attributed to minimization of oxidative damage by improved antioxidant mechanisms and repairing of the membrane damage. In agreement with [38,42], results of EC value with MDA content of this study also confirmed significant positive correlation (0.54 **).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study revealed that primed seeds (HA and HP primed for 3 h and 5 h) had reduced amount of MDA content compared with non-primed seeds believed to be attributed to minimization of oxidative damage by improved antioxidant mechanisms and repairing of the membrane damage. In agreement with [38,42], results of EC value with MDA content of this study also confirmed significant positive correlation (0.54 **).…”
Section: Discussionsupporting
confidence: 92%
“…[15] reported that seed priming enhanced antioxidant defense mechanism of aged seed and consequently reduced cell membrane damage caused by the accumulation of ROS due to lipid peroxidation. This is similar to the findings of [38], in which different priming methods were able to reduce the rate of electrolyte leakage and thereby increased the membrane stability in rice. The results of this study showed that the lowest EC value was recorded in seeds primed for 3 to 5 h (103.4-109.4 µS cm −1 g −1 ), and it was 48-51% reduction compared with non-primed seeds.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pre-sowing seed treatments range from hydropriming, chemical, and biological to physical ones [1]. Improved seed performance in the field has been observed in response to these priming agents in terms of improved germination rate, metabolic pool, and stress-tolerance amongst all halopriming being comparatively easy to manage by a farmer is practiced more than other strategies [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Then, seeds are separated from the matrix and dried to near the initial moisture level. The procedure is flexible (by mixing with other materials), cost-effective, and able to treat a large number of seeds 100 . Important enhancement in crop production has been noted in many reports for the use of MP under environmental stress, such as drought 23 , salinity 101 , and low temperature 102 .…”
Section: Matrix Priming (Mp)mentioning
confidence: 99%